Management of Memorizing the Qur’an Using Qiraati Method at Tahfidz Darul Quran Al Haramain Islamic Boarding School - S. Nor Hasanah (CV. Creative Tugu Pena, 2024)
This research aims to evaluate the effectiveness of the Qiraati method in managing memorizing the Koran at the Tahfidz Darul Quran Al Haramain Islamic Boarding School. The research used a quantitative approach with a survey method, where data was collected from 30 students who were randomly selected and are currently participating in the tahfidz program. The variables measured include memorization speed, retention (memory power), and the students' comfort level with using the Qiraati method. Data analysis was carried out using descriptive and inferential statistical techniques to identify the relationship between the Qiraati method and the students' memorization results. The results showed that the Qiraati method significantly increased memorization speed and retention. Most students feel comfortable and motivated in using this method, which is indicated by the high level of satisfaction. Apart from that, time management and repetition strategies implemented through this method also support the success of the tahfidz program. In conclusion, the Qiraati method has proven to be effective in accelerating and strengthening memorization of the Al-Qur'an in this Islamic boarding school. This research can be a reference for other tahfidz educational institutions in Al-Qur'an learning management.